Parkchain: A Blockchain Powered Parking Solution for Smart Cities - Jennath, H. S.; Adarsh, S.; Chandran, Nikhil V.; Ananthan, R.; Sabir, A.; Asharaf, S. (Frontiers in Blockchain, 2019)
With the advances happening in the area of urbanization, with increased demand for dwellings and an increased number of vehicles on road, finding a parking spot has become one of the major pain points for the citizens. This is mainly due to the limited parking spaces available and difficulty in finding a vacant lot during busy hours. To overcome this limitation, one solution is to create smart parking spaces which are rather easier to find and use. In this work, we propose a Blockchain based solution where parking pools can be created by developing a transparent platform where individuals can rent out their unused land for a stipulated amount of time. A non-fungible token system representing unique parking lots will be created for transparency of the entire system. This also has the added advantage of generating revenue from their otherwise unused property. Smart contracts over Blockchain enforce the contractual agreement between the participants ensuring financial transparency in the proposed system.